The Commercialisation of University Research and Economic Productivity - Clark, Paul (OECD Publishing, 2007)
This article focuses on the relationship between university research (in this case science research) and national economic productivity, particularly in the context of the emerging knowledge economy. It addresses the question of whether university research output should be treated as a public good or a private good, in economic terms, and analyses this question using the tool of game theory. The analysis also draws out the implications both for universities and for governments of treating science as one type of good instead of another